Development of an AlphaLISA assay for sensitive and accurate detection of influenza B virus - Zong, Huijun; Zhang, Shengwei; Shang, Xueyi; Jiang, Hua; Zhao, Zhongpeng; Chen, Shaolong; Wang, Xin; Wang, Ye; Jiang, Yongqiang; Li, Xinyu; Tan, Lingyun; Liu, Peng; et al. (Frontiers in Medicine, 2023)
Objective: Influenza B virus (IBV) is highly contagious, spreads rapidly, and causes seasonal epidemic respiratory disease in the human population, especially in immunocompromised people and young children. Clinical manifestations in this high-risk population are often more severe than in immunocompetent hosts and sometimes atypical. Therefore, rapid, and accurate detection of IBV is important. Methods: An amplified luminescent proximity homogeneous assay linked immunosorbent assay (AlphaLISA) was developed for detection of IBV by optimizing the ratio of IBV antibody-labeled receptor beads, streptavidin-conjugated donor beads and biotinylated IBV antibody, as well as the optimal temperature and time conditions for incubation. Assay sensitivity, specificity and reproducibility were evaluated. A total of 228 throat swab samples and inactivated IBV were tested by AlphaLISA and lateral flow colloidal gold-based immunoassay (LFIA), which is common method in clinical practice. Results: AlphaLISA produced the best results for detection of IBV when IBV antibody-labeled acceptor beads were 50 μg/ mL, streptavidin-conjugated donor beads were 40μg/ mL, and biotinylated IBV antibody was diluted 0.5μg/mL at 37℃ for 15-10 minutes. Under these conditions, AlphaLISA had a limit of detection of 0.24 ng/mL for the detection of influenza B nucleoprotein, did not cross react with other common respiratory viruses, and showed good reproducibility with inter-assay coefficient of variation (CV) and intra-assay CV < 5%. The results of 228 clinical throat swab samples showed good agreement between AlphaLISA and LFIA (Kappa=0.982), and AlphaLISA showed better sensitivity than LFIA for detecting inactivated IBV. Conclusion: AlphaLISA showed higher sensitivity and throughput in the detection of IBV and can be used for IBV diagnosis and epidemic control.